Nuclear Smad6 promotes gliomagenesis by negatively regulating PIAS3-mediated STAT3 inhibition - Jiao, Jiantong; Zhang, Rui; Li, Zheng; Yin, Ying; Fang, Xiangming; Ding, Xiaopeng; Cai, Ying; Yang, Shudong; Mu, Huijun; Zong, Da; Chen, Yuexin; Zhang, Yansong; et al. (Nature communications, 2018)
To date, the molecular mechanism underlying constitutive signal transducer and activator of transcription 3 (STAT3) activation in gliomas is largely unclear. In this study, we report that Smad6 is overexpressed in nuclei of glioma cells, which correlates with poor patient survival and regulates STAT3 activity via negatively regulating the Protein Inhibitors of Activated STAT3 (PIAS3). Mechanically, Smad6 interacts directly with PIAS3, and this interaction is mediated through the Mad homology 2 (MH2) domain of Smad6 and the Ring domain of PIAS3. Smad6 recruits Smurf1 to facilitate PIAS3 ubiquitination and degradation, which also depends on the MH2 domain and the PY motif of Smad6. Consequently, Smad6 reduces PIAS3-mediated STAT3 inhibition and promotes glioma cell growth and stem-like cell initiation. Moreover, the Smad6 MH2 transducible protein restores PIAS3 expression and subsequently reduces gliomagenesis. Collectively, we conclude that nuclear-Smad6 enhances glioma development by inducing PIAS3 degradation and subsequent STAT3 activity upregulation. In glioma STAT3 signaling contributes to gliomagenesis. Here, the authors show that Smad6 expression correlates with poor survival and is overexpressed in glioma cells, and regulates STAT3 activity via negatively regulating PIAS3.